Multiple-layered anti-counterfeit labels - Tan, Richard (Nanyang Technological University, 2021)
Anti-counterfeit technology has been intense research in recent years because of the increasing number of counterfeit goods in the industry. Besides affecting the reputation of a company, counterfeit goods affect the wellbeing and safety of the consumer. To help prevent counterfeit products from reaching retailers, the manufacturer has implemented several anti-counterfeit labels to authenticate products. However, most of the recent anti-counterfeit labels technology has been mastered by the outside world. Given, most of the labels are not responsive to heat. Illegal operators could remove the original labels using heat before reproducing identical labels. A series of research and experiment were conducted to explore ways of creating a heat responsive anti-counterfeit label. The research includes producing a unique watermark on a PVC sample using aluminium tape and soldering iron. The number of aluminium tape and foil was determined to produce the best result without melting the PVC through testing. Secondly, creating permanent indentation on the PVC with sharp and shallow brass mould will change upon contact with heat. It was concluded at various temperatures, depending on the type of mould, the indentation will change. Besides creating permanent indentations labels for anti-counterfeit applications, the labels can be used as a temperature indication for disinfection of beverages such as milk and wine. Furthermore, a series of techniques mentioned earlier could be combined into a single PVC label to produce multi-layered anti-counterfeit labels and other applications. Hence, this research has allowed for new questions and test to be conducted, bringing it closer to commercializing it.